Lexical-Functional Grammar of the Croatian Language: Theoretical and Practical Models - Seljan, Sanja (Array, 2003)
Formal description aims to find the most suitable way to formalize a certain segment of the language, or some language phenomena at morphological, lexical, syntactic or semantic level. There is a variety of formal models based on different approaches in order describe the natural language as much as possible. One type of such formal model is described in the thesis entitled “ Lexical-Functional Grammar of the Croatian Language: Theoretical and Practical Models” . The aim of this work was: a) To find the theoretical formal models and to define formal rules in order to describe certain language phenomena at the morphological, lexical, syntactic and semantic level for the subset of Croatian language sentences. b) To verify computationally theoretical models using LFGW program in Amzi Prolog The method used for the formal description of the Croatian is Lexical-Functional Grammar which is generative non-transformational grammar, belonging to the group of Unification Grammars. The hypothesis to verify is definition of the LFG model as context-sensitive grammar or the grammar on the basis of constraints according to which it should be suitable for introduction of new characteristic features and for the description of language with relatively free word order.